In vivo study of compounds 3-(acetyl Salicyloyl)-5,6 –Oisopropylidene-L-ascorbic acid ,2,3- (acetyl Salicyloyl)-5,6 –O-isopropylidene-L-ascorbic acid and 2,3,5,6Tetra(acetyl Salicyloyl)-L-ascorbic acid - Maher, F. T.; Mukhlis, A-J.; Abuod, A. I.; Naji, N. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In vivo study was made for the coumpounds 3-(ocetyl Salicyloyl)-5,6-O-isoprpy lideneL-ascorbicocid,2,3-(acetyl Salicyloyl )-5,6-o- isopropylidene-L-ascorbic acid and 2,3,5,6(acetyl Salicyloyl )-L- ascorbic acid .And a measurement was mod for the concentration of the liberated aspirin in blood samples a fter (2,3,4,6,8,10) hours of the initial dose for the animal .The results showed that the highest concentration of aspirin was after four hours of giving the dose to the animal which is in accordance with pharmacokinetics studies